Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1515/dmdi.2007.22.2-3.175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silymarin on the Oral Bioavailability of Ranitidine in Healthy Human Volunteers

Abstract: The effect of silymarin pretreatment on the pharmacokinetics of ranitidine was investigated in 12 healthy male human volunteers aged 19-26 years. After an overnight fast, ranitidine 150 mg was administered to the volunteers either alone or after 7 days pretreatment with thrice daily dose of 140 mg silymarin. The wash-out period between each treatment was 7 days. Serum levels of ranitidine were determined by HPLC. Pharmacokinetic parameters were determined based on non-compartmental model analysis using the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In contrast, milk thistle did not alter the pharmacokinetics of nifedipine [179], digoxin [180], indinavir [181], rosuvastatin [182], debrisoquine [183], ranitidine [184], and midazolam [185] in humans. It appears milk thistle does not affect the activity of CYP3A4 and P-gp in vivo.…”
Section: Irinotecan + Milk Thistlementioning
confidence: 78%
“…In contrast, milk thistle did not alter the pharmacokinetics of nifedipine [179], digoxin [180], indinavir [181], rosuvastatin [182], debrisoquine [183], ranitidine [184], and midazolam [185] in humans. It appears milk thistle does not affect the activity of CYP3A4 and P-gp in vivo.…”
Section: Irinotecan + Milk Thistlementioning
confidence: 78%
“…In vitro studies have shown that silymarin, in higher concentrations, has a strong inhibitory effect on both P450 3A4 [56–58] and P‐gp [59–61]. The concentration tested in vitro exceeded physiologically attainable levels [56–58, 60, 61] and hence previous studies in vivo have shown no to mild inhibition effects when co‐administered with ranitidine [62], nifedipine [63], midazolam [64] and indinavir [65, 66] in healthy volunteers. Recently, Schrieber et al.…”
Section: Discussionmentioning
confidence: 91%
“…Rao et al demonstrated the effect of silymarin pretreatment on the pharmacokinetics of ranitidine was investigated in healthy male human volunteers. There was no influence of silymarin on the C max and AUC, significant difference in area under the first moment curve (AUMC) and mean residence time of ranitidine (Rao et al, 2007).…”
Section: Ranitidinementioning
confidence: 91%